HUBUNGAN ANTARA KEPUASAN KERJA DENGAN KINERJA PERAWAT DI RS TENTARA TK IV 010701 PEMATANGSIANTAR - Damanik, Dermawani (Universitas Prima Indonesia, 2019)
Nurse job performance is one of the factors that influence service quality in implementing nursing care. Nurse job satisfaction is an important part of life that influences productivity performance and the quality of care provided. The purpose of this study is to examine the relationship between work satisfaction and nurse job performance in Army TK IV Hospital 010701 Pematangsiantar. Type of research is correlation descriptive study. The population in this study were nurses working in the inpatient room. The sampling technique was done by simple random sampling, which was 84 respondents. The instrument in this study used a questionnaire made by the researcher himself. The job satisfaction questionnaire consisted of 32 statements while the nurse job performance questionnaire consisted of 10 statements. Test statistics using Rho spearmen. The results of the research conducted at TK IV 010701 Army Hospital Pematangsiantar obtained that the majority of nurses 'job satisfaction was in the sufficient category as many as 63 respondents (75%), the majority of nurses' performance were in the moderate category, 44 respondents (52.4%), analysis with the SPSS program was value p <0.05 which is equal to 0.000, meaning that there is a meaningful correlation, which means there is a relationship between job satisfaction and the job performance of nurses in Army TK IV Hospital 010701 Pematangsiantar. It is recommended that the management of the Hospital need to pay attention to and establish strategies to improve job satisfaction for nurses because nurses are the largest human resource in the health care system.